Peningkatan Produktivitas Kacang Tanah Melalui Penerapan Komponen Teknologi Kunci - Eman Paturohman; Sumarno Sumarno (Puslitbang Tanaman Pangan, 2014)
Groundnut is a legume crop which is widely distributed in the tropical countries. Of the total world harvested area of 29.4 million ha, tropical countries in Asia and Africa accounted for 92%, while in North America, Central and South America only 5.6%. The productivities of groundnut in the world vary greatly, from 0.5 t/ha to 3.5 t/ha dry pod. The main limiting factors for groundnut productivity are drought stress and diseases incidences, especially leaf spot (Cercospora sp). Critical stage for water shortages which greatly reduces productivity is during the generative stadia, which starts from flowering to pod filling. For spanish type varieties which are widely planted in Indonesia, critical phase occurs at age from 35 to 80 days. The productivity of groundnut in Indonesia is low, similar to that in India, Ghana and Nigeria, the major groundnut producers in the world. Although many factors account for the low groundnut yield in Indonesia, the inadequate soil moisture and leaf diseases are considered as the two main causes. To improve the productivity of groundnut at the existing production centers, the provision of supplemental irrigation or by way of planting time adjustment so that the rainfalls supply sufficient soil moisture during the generative phase, followed by leaf disease control, are the two keys technology components that need to be adopted. Appropriate planting time and applying fungicide to control leaf diseases at about 50 and 65 days after planting, produced yield up to 2 t/ha dry pods or 1.5 t/ha of dry kernel. Advanced technology consisted of deep soil tillage, planting seeds on the ridges, mulching (covering the ridges) with polyethen plastic and supplementing irrigation, as is done in China, could obtain maximum productivity of 6 t to 8 t/ha dry pods. This technology needs to be tested in Indonesia to overcome the present groundnut stagnant low productivity.